Caffeine, but not paracetamol (acetaminophen), enhances muscular endurance, strength, and power - Bela Scapec; Jozo Grgic; Dorian Varovic; Pavle Mikulic (Journal of the International Society of Sports Nutrition)
Background Caffeine is one of the most popular ergogenic aids consumed by athletes. Caffeine’s ergogenic effect has been generally explained by its ability to bind to adenosine receptors, thus modulating pain and reducing perceived exertion. Another pharmacological agent that may improve performance due to its analgesic proprieties is paracetamol. This study aimed to explore the effects of caffeine, paracetamol, and caffeine + paracetamol consumption on muscular endurance, strength, power, anaerobic endurance, and jumping performance.Methods In this randomized, crossover, double-blind study, 29 resistance-trained participants (11 men and 18 women) ingested either a placebo, caffeine (3 mg/kg), paracetamol (1500 mg) or caffeine + paracetamol 45 min before the testing sessions. The testing sessions included performing the bench press exercise with 75% of one-repetition maximum to momentary muscular failure, isokinetic knee extension and flexion at angular velocities of 60°/sec and 180°/sec, Wingate, and countermovement jump (CMJ) tests.Results Compared to placebo, isolated caffeine ingestion increased the number of repetitions performed in the bench press (p = 0.005; d = 0.42). Compared to placebo, isolated caffeine ingestion and/or caffeine + paracetamol consumption was ergogenic for strength (torque), muscular endurance (total work), or power in the isokinetic assessment, particularly at slower angular velocities (p = 0.027 to 0.002; d = 0.16 to 0.26). No significant differences between the conditions were observed for outcomes related to the Wingate and CMJ tests.Conclusion This study provided novel evidence into the effectiveness of caffeine, paracetamol, and their combination on exercise performance. We found improvements in muscular endurance, strength, or power only when caffeine was consumed in isolation, or in combination with paracetamol. Isolated paracetamol consumption did not improve performance for any of the analyzed outcomes, thus calling into question its ergogenic potential.